Memories liberate the past - Thesnaar, CH (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Memory is central in dealing with and being liberated from the trauma of the past. Individuals, families, communities and nations have struggled through the centuries to face and deal with their memories in a constructive way. Memory is thus indispensable for living in the present and hoping for a reconciled future if people toreconcile with God, with those closest to them, with others and with themselves. This article argues that memory is a key element within the healing and reconciliation process for victims and perpetrators. To reach this goal the significance and content of memory need to be ascertained and understood.